Customer Decisions in Islamic Gold Pawning: The Role of Service Excellence and Sharia Compliance in Rural Indonesia - Argantara, Zaid Raya; Sa’adah, Qanitatus (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2025)
The development of the Islamic banking industry demands excellent service and consistent implementation of Islamic governance principles to maintain and increase customer trust. Islamic People's Financing Banks (BPRS), although the institution is between commercial banks and microfinance institutions, are required to be able to compete through service excellence and Islamic compliance. This study aims to determine the effect of excellent service and Islamic governance on customer decisions in using gold pawn products at BPRS Bhakti Sumekar KCP Pragaan. This study uses a quantitative approach with multiple linear regression analysis techniques. The sample was taken using probability sampling techniques, with 46 respondents who were active users of gold pawn products. Data were collected through a structured questionnaire. The results of the study indicate that the two independent variables, namely excellent service and Islamic governance, have a positive and significant effect on customer decisions. Simultaneously, the two variables contribute 95.8% to customer decision making, while the remaining 4.2% is influenced by other factors outside the research model. The novelty of this research lies in the integrative focus between service and sharia aspects in the context of gold pawn products at BPRS, which has not been studied empirically in previous literature, especially in rural areas such as Pragaan.